Answer

Verified

484.8k+ views

Hint: For finding the value of $f(x + 3),$put $x + 3$in place of $x$in $f(x).$

The given function in the question is $f(x) = {x^4} - 12{x^3} + 17{x^2} - 9x + 7$

For $f(x + 3),$we will replace $x$with $x + 3,$we’ll get:

$ \Rightarrow f(x + 3) = {(x + 3)^4} - 12{(x + 3)^3} + 17{(x + 3)^2} - 9(x + 3) + 7$

For ${(x + 3)^4},$we’ll use binomial expansion and for rest of the terms we use formulae as:

$

{(a + b)^3} = {a^3} + {b^3} + 3ab(a + b) \\

{(a + b)^2} = {a^2} + {b^2} + 2ab \\

$

Using these results, we’ll get:

\[

\Rightarrow f(x + 3) = {(^4}{C_0}{x^4}{ + ^4}{C_1}{x^3}.3{ + ^4}{C_2}{x^2}{.3^2}{ + ^4}{C_3}x{.3^3}{ + ^4}{C_4}{.3^4}) - 12({x^3} + {3^3} + 3 \times x \times 3(x + 3)) \\

{\text{ }} + 17({x^2} + 9 + 6x) - 9(x + 3) + 7 \\

\Rightarrow f(x + 3) = ({x^4} + 12{x^3} + 54{x^2} + 108x + 81) - 12({x^3} + 9{x^2} + 27x + 27) + 17{x^2} + 153 + 102x - 9x - 27 + 7 \\

\Rightarrow f(x + 3) = {x^4} + 12{x^3} - 12{x^3} + 54{x^2} - 108{x^2} + 17{x^2} + 108x - 324x + 102x - 9x + 81 - 324 + 153 - 27 + 7 \\

\Rightarrow f(x + 3) = {x^4} - 37{x^2} - 123x - 110 \\

\]

Therefore, the final value of $f(x + 3)$is \[{x^4} - 37{x^2} - 123x - 110\]

Note: For ${(x + 3)^4},$instead of using binomial expansion we can also use general expansion method as:

${(x + 3)^4} = {(x + 3)^2}.{(x + 3)^2},$

${(x + 3)^4} = ({x^2} + 9 + 6x).({x^2} + 9 + 6x)$and we can multiply it step by step. We’ll get the same result.

The given function in the question is $f(x) = {x^4} - 12{x^3} + 17{x^2} - 9x + 7$

For $f(x + 3),$we will replace $x$with $x + 3,$we’ll get:

$ \Rightarrow f(x + 3) = {(x + 3)^4} - 12{(x + 3)^3} + 17{(x + 3)^2} - 9(x + 3) + 7$

For ${(x + 3)^4},$we’ll use binomial expansion and for rest of the terms we use formulae as:

$

{(a + b)^3} = {a^3} + {b^3} + 3ab(a + b) \\

{(a + b)^2} = {a^2} + {b^2} + 2ab \\

$

Using these results, we’ll get:

\[

\Rightarrow f(x + 3) = {(^4}{C_0}{x^4}{ + ^4}{C_1}{x^3}.3{ + ^4}{C_2}{x^2}{.3^2}{ + ^4}{C_3}x{.3^3}{ + ^4}{C_4}{.3^4}) - 12({x^3} + {3^3} + 3 \times x \times 3(x + 3)) \\

{\text{ }} + 17({x^2} + 9 + 6x) - 9(x + 3) + 7 \\

\Rightarrow f(x + 3) = ({x^4} + 12{x^3} + 54{x^2} + 108x + 81) - 12({x^3} + 9{x^2} + 27x + 27) + 17{x^2} + 153 + 102x - 9x - 27 + 7 \\

\Rightarrow f(x + 3) = {x^4} + 12{x^3} - 12{x^3} + 54{x^2} - 108{x^2} + 17{x^2} + 108x - 324x + 102x - 9x + 81 - 324 + 153 - 27 + 7 \\

\Rightarrow f(x + 3) = {x^4} - 37{x^2} - 123x - 110 \\

\]

Therefore, the final value of $f(x + 3)$is \[{x^4} - 37{x^2} - 123x - 110\]

Note: For ${(x + 3)^4},$instead of using binomial expansion we can also use general expansion method as:

${(x + 3)^4} = {(x + 3)^2}.{(x + 3)^2},$

${(x + 3)^4} = ({x^2} + 9 + 6x).({x^2} + 9 + 6x)$and we can multiply it step by step. We’ll get the same result.

Recently Updated Pages

what is the correct chronological order of the following class 10 social science CBSE

Which of the following was not the actual cause for class 10 social science CBSE

Which of the following statements is not correct A class 10 social science CBSE

Which of the following leaders was not present in the class 10 social science CBSE

Garampani Sanctuary is located at A Diphu Assam B Gangtok class 10 social science CBSE

Which one of the following places is not covered by class 10 social science CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

The states of India which do not have an International class 10 social science CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

How do you graph the function fx 4x class 9 maths CBSE

One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE

Difference Between Plant Cell and Animal Cell

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Why is there a time difference of about 5 hours between class 10 social science CBSE

Name the three parallel ranges of the Himalayas Describe class 9 social science CBSE